HISTORICAL TRANSFORMATION OF CITIZENSHIP THOUGHT: CLASSICAL, MODERN, CONTEMPORARY - Bambang Yuniarto; Fajar Nurul Ikhlas; Mutiara Sapira Putri; Ihsan Ali Multazam; Deris Ardian; Muhammad Indera Wiguna (International Journal of Teaching and Learning, 2025)
This study aims to analyze the historical transformation of citizenship thought from the classical, modern, to contemporary eras, and to understand the dynamics of changes in the concept of citizenship alongside social, political, and intellectual developments. The objective of this study is to identify the philosophical and structural turning points that have shaped the understanding of citizenship. The main problem of this research lies in the lack of comprehensive studies that integrally discuss the evolution of citizenship across periods, thus necessitating a study capable of systematically explaining the continuities and shifts in ideas. The limitations of previous studies often separate historical periods, failing to capture the evolutionary narrative. The method used is a qualitative descriptive-historical approach with a literature study that examines the works of classical, modern, and contemporary thinkers, analyzed through content analysis and comparative analysis techniques to identify patterns of thought change. The results show that the classical era emphasized virtue, morality, and active participation in public life, while the modern era shifted the focus to individual rights, the social contract, and the legal status of citizens. In the contemporary era, the concept of citizenship has evolved to become more inclusive, global, and multicultural, and is significantly influenced by digitalization and transnational mobility. Overall, this research confirms that changes in citizenship thought reflect the dynamic relationship between the individual, the state, and the global community, and have important implications for developing adaptive, critical citizenship education that is relevant to global challenges.